2005
DOI: 10.1007/s11178-005-0162-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvents on a Catalyzed Reaction between Aniline and Benzoic Acid

Abstract: We formerly studied [16] synthetic approaches, the effect of substituents and catalysts on reactions of direct acylation, namely on formation of anilides in reactions of aromatic amines with aromatic carboxylic acids.Here we report on investigation of the solvent effect on the model reaction (1) in the presence of activated [5] titanium(IV) butoxide (0.02 mol per 1 mol of benzoic acid) aimed at finding optimum conditions for anilides synthesis.Reaction (1) can proceed only at vigorous boiling and distilling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the presence of polar solvents such as DMF, DMSO, HMPA and sulfolane, the amidation reaction was inhibited even at 10 mol% 100 concentration in o-xylene. 93 Shteinberg et al observed that batches of the Ti(OBu) 4 catalyst which had been standing on the shelf for some time seemed to perform better than freshly distilled ones. The authors attributed 105 this effect to the involvement of water at some stage in the reaction and therefore investigated the catalytic activity of aged batches of the catalyst.…”
mentioning
confidence: 99%
“…In the presence of polar solvents such as DMF, DMSO, HMPA and sulfolane, the amidation reaction was inhibited even at 10 mol% 100 concentration in o-xylene. 93 Shteinberg et al observed that batches of the Ti(OBu) 4 catalyst which had been standing on the shelf for some time seemed to perform better than freshly distilled ones. The authors attributed 105 this effect to the involvement of water at some stage in the reaction and therefore investigated the catalytic activity of aged batches of the catalyst.…”
mentioning
confidence: 99%
“…Applying the conditions used in the initial catalyst screen, the most suitable solvent was determined (Table S2, see ESI ‡). Dipolar aprotic solvents, DMF and DMSO, showed low conversions, 71,99 whilst polar solvents such as CPME (cyclopentylmethylether), isoamyl alcohol and butyronitrile revealed reasonable conversions. The use of non-polar solvents such as toluene and octane showed the highest conversions into the corresponding amide.…”
Section: Magnesium Salts As Catalystmentioning
confidence: 99%
“…Ti(OBu) 4 ‐catalyzed amidation of carboxylic acids with aromatic amines, aniline and its derivatives, upon boiling in xylene or aniline, was carried out by Shteinberg [35–42] . Shteinberg also demonstrated that the Ti(OBu) 4 ‐catalyzed reaction of 4‐nitrobenzoic acid with ammonia in the presence of polyethylene glycol 400 is followed by the formation of the primary amide, 4‐nitrobenzamide, in high yield [43] . The amidation of carboxylic acids with dialkylammonium dialkylcarbamate in the presence of activated 4 A molecular sieves and 20 mol % TiCl 4 or ZrCl 4 involves formation of amides as well [44,45] .…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic amounts of various Ti(IV)‐complexes were used to prepare N , N ‐dimethyl‐ m ‐tolylamide in the reaction of 3‐methylbenzoic acid with dimethylamine at 150–300 °C [34,35] . Ti(OBu) 4 ‐catalyzed amidation of carboxylic acids with aromatic amines, aniline and its derivatives, upon boiling in xylene or aniline, was carried out by Shteinberg [35–42] . Shteinberg also demonstrated that the Ti(OBu) 4 ‐catalyzed reaction of 4‐nitrobenzoic acid with ammonia in the presence of polyethylene glycol 400 is followed by the formation of the primary amide, 4‐nitrobenzamide, in high yield [43] .…”
Section: Introductionmentioning
confidence: 99%